Communication and Mass Media Complete. (S.l. : s.n.)
EBSCO-database over reclame, marketing,film/video, gamestudies, journalistiek, communicatie, massamedia,taalkunde, retoriek, taal, logica ... // EBSCO database covering advertising, marketing, film/video, game studies, journalism, communication, mass media, linguistics, rhetoric, language, logic, and other closely related fields.
Keywords: Communicatie; Journalistiek